Twin pregnancies and perinatal outcomes: a comparison between fresh and frozen embryo transfer: a two-centre study. Issue 2 (February 2019) - Shavit, Maya; Miller, Netanella; Schreiber, Hanoch; Asali, Aula; Ravid, Dorit; Harlev, Avi; Levitas, Eliahu; Har-Vardi, Iris; Berkovitz, Arie
Highlights: Twin pregnancies resulting from frozen embryo transfer have better perinatal outcome. The 'frozen' group had higher birthweight and lower risk of low birthweight infants. The 'frozen' group had lower incidence of spontaneous second trimester miscarriage. No difference was found between groups regarding gestational age at birth. Abstract: Research question: To assess the perinatal and obstetric outcomes of twin pregnancies resulting from IVF frozen embryo transfer (FET) in comparison with fresh embryo transfer. Design: A retrospective cohort study of 773 twin pregnancies conceived via IVF treatment. Data were collected from the records of two outpatient fertility IVF clinics of cycles conducted between 2006 and 2016. Results: A total of 773 pregnancies were evaluated: 614 (79.4%) following FET and 159 (20.6%) following fresh embryo transfer. The FET group had a significantly higher mean birthweight ( P = 0.002), and lower rates of small for gestational age ( P = 0.003), low ( P = 0.003) and very low birthweight ( P = 0.006) infants. Also, a significantly lower rate of spontaneous second trimester miscarriage compared with the fresh embryo transfer group was observed ( P = 0.001). No significant difference was found between groups regarding gestational age at delivery, term birth (after 37 weeks of gestation), twin discordancy rate, fetal major malformation rate, and hospitalization duration. Conclusion: In twin pregnancies, FET might have better perinatal outcomes compared with fresh embryo transfer in regards to birthweight and spontaneous second trimester miscarriages. Further research is needed to evaluate these results.